重症心不全に対する補助人工心臓治療 - 田中, 正史; 奥村, 恭男; 瀬在, 明 (日大医学雑誌, 2020)
A ventricular assist device (VAD) is an artificial organ that assists the function of the left and/or right ventricleof the heart in patients with severe heart failure. In 1982, our hospital was the first to achieve successful use of aVAD in Japan. There are still only 4 institutions in Tokyo to which accreditation was granted for the use of implantable VADs. We would like to present our current clinical experience with VAD therapy and future prospects.The INTERMACS registry includes 25,087 patients who underwent VAD therapy as of May 2020, while theJ-MACS registry (Japan) includes 945 patients as of June 2019. Recent reports have indicated that a drastic shiftoccurred from pulsatile pumps to continuous flow pumps and that the timing of implantation also changed, i.e.,earlier implantation in mild patients or at a high INTERMACS level. This is a global trend.More than 6 decades have elapsed since the introduction of VADs. With advancement in a cutting-edge technology, VAD therapy has become an important treatment option for severe heart failure. In Western countries,implantable VADs are regarded as an alternative to heart transplantation, and the bridge to transplantation ratio hasdeclined while the destination therapy (DT) ratio has increased. Since it is anticipated that DT will be approvedin Japan in a few years, it is expected that DT will become popular in Japan, where heart transplantation is infrequently conducted.